Interleukin-10 −592C/A, but not −1082A/G promoter single nucleotide polymorphism, is associated with a decreased risk of colorectal cancer in an ethnic Kashmiri population: a case–control study. Issue 6 (November 2017) - Banday, Mujeeb Z.; Sameer, Aga S.; Chowdri, Nissar A.; Haq, Ehtishamul
Abstract : Chronic inflammation influences the development of various cancers including colorectal cancer (CRC). Interleukin-10 (IL-10), an anti-inflammatory cytokine, plays a vital role in several homeostatic physiological processes occurring in the human gastrointestinal tract including intestinal inflammation and is a key regulator of several gastrointestinal tract pathophysiological processes such as inflammatory bowel diseases that are associated with an increased predisposition to CRC. Several studies have reported the association of various polymorphisms in the human IL-10 gene including IL-10 −592C/A and IL-10 −1082A/G single nucleotide polymorphisms (SNPs) with various cancers including CRC, but these SNPs are yet to be studied in a Kashmiri population with respect to CRC risk. The aim of this study was to analyze the association of IL-10 −592C/A and IL-10 −1082A/G promoter SNPs with CRC risk in an ethnic Kashmiri population through a case–control design. The genotype frequencies of IL-10 −592C/A and IL-10 −1082A/G promoter SNPs were compared between 142 CRC patients and 184 individually matched healthy controls using the PCR and restriction fragment length polymorphism method. The association between the IL-10 −592C/A and IL-10 −1082A/G SNPs and CRC risk was examined through conditional logistic regression models adjusted for multiple possible confounding (third) variables. The possible effect measure modification of the association between the relevant SNP genotypes and CRC risk by various CRC risk factors including age, sex, and smoking status was also evaluated. Further, the associations between these SNPs and various clinicopathological parameters, demographic variables, and environmental factors in the case group patients with respect to CRC risk were also analyzed. The overall association between the IL-10 −592C/A SNP and the modulation of CRC risk was found to be significant ( P =0.001). The variant genotype (AA) was significantly associated with a decreased risk of CRC (odds ratio: 0.25; 95% confidence interval: 0.11–0.61; P =0.002). Further, the less common IL-10 −592A allele was associated with a decreased risk of CRC (odds ratio: 0.64; 95% confidence interval: 0.46–0.88; P =0.0092). The overall association between the IL-10 −1082A/G SNP and the modulation of CRC risk was not found to be significant ( P =0.141). This study has shown that there is a significant association between the IL-10 −592C/A promoter SNP and a decreased risk of CRC in an ethnic Kashmiri population, but the association between IL-10 −1082A/G SNP and the risk of CRC in the population under study is not significant. However, to substantiate our findings, this study needs to be replicated with a larger sample size and with other ethnically defined populations with comparable CRC incidence. Abstract : Supplemental Digital Content is available in the text.